Estrazioni nel paesaggio - Rosa Barba i Casanovas (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
“Scientific knowledge, aesthetic emotion, theory and technique, as arms to make possible our partecipation in the world. We put all this together, what we have and what presents with evidence the making of glances fixing our knowledge and settinguo a tool of communication and culture. Eyes from near and far, on which we can find and remind, on landscapes that belong to who live and dream”.With these words Rosa Barba introduces the book Paisatge de les pedreres de Menorca. Restauració i intervencions, in which we find her article Pedreres en el paisatge that we are publishing now in Italian. For Rosa Barba talking about Minorca’s quarries is the chance for a more general discussion on the relation between natural elements and processes and human activities in building the landscape and on the implication that the stratigraphy of this double action has on transformation and rehabilitation projects of these sites.